NETs: a new target for autoimmune disease - Tang, Ran; Yin, Jiahua; Qin, Zhifang; Zhang, Min; Jia, Xiaoyi (Frontiers in Immunology, 2025)
Neutrophil extracellular traps (NETs) are reticular fiber structures released by neutrophils in response to various stimuli. Although NETs have antibacterial defense functions, their excessive formation has been proven to accelerate the progression of autoimmune diseases. Increasing studies have shown that NETs play an important role in the pathogenesis of autoimmune diseases. The pathogenesis of recent advances in autoimmune disease research, with a focus on the role of NETs in the etiology and pathogenesis of these disorders, and summarizes the current treatment strategies targeting NETs, aiming to provide new directions for the treatment of autoimmune diseases.